2021
DOI: 10.1504/ijesd.2021.112666
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of health and economic costs on street children working as waste collectors in Dhaka City

Abstract: This research investigates the health impacts and access to health services by children who are engaged in waste collection in Dhaka, the capital city of Bangladesh. The relevant qualitative data were collected through expert interviews and personal observations, while quantitative data were gathered through a face-to-face questionnaire survey given to 50 street children who collected waste at the landfill site located in Dhaka city's Matuail area. The results indicate that 94% of these children have suffered … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…This shows that the overall injury rate was very high in the South Asian region. Six of the studies reported cuts, which ranged up to 84.0%, the highest being in India [ 14 , 15 , 17 , 21 , 22 , 23 ]. Dog bites and insect bites were also frequent.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This shows that the overall injury rate was very high in the South Asian region. Six of the studies reported cuts, which ranged up to 84.0%, the highest being in India [ 14 , 15 , 17 , 21 , 22 , 23 ]. Dog bites and insect bites were also frequent.…”
Section: Resultsmentioning
confidence: 99%
“…Children suffered from a variety of skin problems as a result of their exposure to waste [ 23 ]. Skin problems affected 5.7% to 97.3% of those polled [ 14 , 15 , 17 , 18 , 23 ]. The main reason behind this wide range was the definition of skin problems, which varied among the studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations